Evaluation of the Anti-Bacterial Potential of Allium Sativum Against some Resistant Human Pathogenic Isolates and its Synergy with Antibiotics - Sahiba Gul, Shakila Bibi, Haseena Nazneen, Muhammad Adeel Alam, Ansa Khan, Zahid Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Allium Sativum has long been considered one of the most efficient medicinal plants for treating bacterial illness. Taking into consideration the current research study was conducted to assess the effect of Allium sativum extract on Multi-Drug Resistant (MDR) bacterial isolates and its association with antibiotics against MDR pathogens commonly found in the hospital environment. Methods: The test organisms (Staph aureus, Staphylococcus, Yersinia, Micrococcus) which were clinically isolated from patients were collected from Lady Reading Hospital Peshawar. The clinical samples were cultured into their defined media. The disc diffusion method was used to test the antibiotic susceptibility of Meropenem, Ciprofloxacin, Cefixime, Ampicillin, and Erythromycin. Antibacterial activity was performed by using the agar well diffusion method. Four different solvents (methanol, n-hexane, ethyl acetate, and distilled water) were used to extract the bioactive compounds of Allium sativum. The synergistic activity of fresh garlic extracts and antibiotics was performed by disc diffusion assay using antibiotic and extract at the same time. Results: Out of 25 samples, 7 samples (Yersinia, Staphylococcus, and Micrococcus species) were MDR to antibiotics. A high level of sensitivity of microbes was recorded for MEM. Depending on the susceptibility of fresh garlic extract, the aqueous extract showed a maximum zone of inhibition of 42mm against Yersinia compared to the conventional antibiotic Ciprofloxacin which showed resistance. The minimum zone of inhibition of 10mm showed against Micrococcus. Ethyl acetate extract showed a maximum zone of inhibition of 30mm against staphylococcus while a minimum zone of inhibition of 11mm against Micrococcus. Methanolic extract showed a maximum zone of inhibition of 21mm against staphylococcus while a minimum zone of inhibition of 12 against Micrococcus and other isolates. N-hexane extract showed the lowest activity among all extracts. Fresh garlic extract inhibited MDR isolates demonstrating a synergistic association with antibiotics. Practical Implication: The potential use of such a combination may be beneficial especially in inhibiting drug-resistant pathogens. Based on the results of this study, taking garlic as a supplement during antibiotic therapy improves its efficiency. Conclusion: Garlic extracts showed good activity against selected MDR isolates. Aqueous extract and ethyl acetate extract showed maximum activity against MDR bacterial isolates. This study also showed good synergistic activity of garlic extracts in combination with antibiotics while no antagonistic activity has been shown. Keywords: Allium sativum, Antibacterial activity, MDR, Fresh Garlic Extract, Synergy